A propósito del servicio militar voluntario peruano: Una revisión de los últimos debates que abordan el ejercicio constitucional en el Perú contemporáneo - Morales Tinta, Stefany (Pontificia Universidad Católica del Perú, 2022)
With the arrival of the pandemic due to Covid-19, the worsening of citizen insecurity and the rise of the new government, the nature of voluntary military service has been debated, seeking to make it part of a public policy that addresses young people. Against this background, at the social level some debates have been developed that point out before the importance of understanding the structural bases of youth. Starting from this approach, the following paper presents a review that shows the trajectory and scope of the exercise of voluntary military service in contemporary Peru. The structure of the text is based on two thematic axes: studies and approaches to military service and military service in the political agendas of governments. Interest in the exercise of military service in Latin America and its variants is part of a large body of research and there is a varied literature on the historical notion of military service. However, only in some cases have social aspects been considered in a very superficial way and not directly related to military service, but with respect to the profession. Given this absence, it is hoped to contribute with a scope that highlights this often invisible and complex space, considering that it can be promising in terms of data for the analysis of political decisions that lead to strengthening the actions of the Armed Forces institutions by time to convene volunteer military personnel and future public policies for youth.

Con la llegada de la pandemia a causa del Covid-19, la agudización de la inseguridad ciudadana y el ascenso del nuevo gobierno se ha puesto en debate el carácter del servicio militar voluntario, buscando que pase a formar parte de una política pública que aborde a la juventud. Frente a este contexto, a nivel social se han desarrollado algunos debates que señalan antes, la importancia de comprender las bases estructurales de la juventud. Partiendo de este enfoque, en el siguiente trabajo se presenta una revisión que evidencia la trayectoria, y alcances sobre el ejercicio del servicio militar voluntario en el Perú contemporáneo. Para la estructura del texto, se parte de dos ejes temáticos: los estudios y abordajes del servicio militar y el servicio militar en las agendas políticas de los gobiernos. El interés en el ejercicio del servicio militar en Latinoamérica y sus variantes forma parte de un grueso de investigaciones y existe una literatura variada sobre la noción histórica del servicio militar. Sin embargo, solo en algunos casos se ha considerado aspectos sociales de forma muy superficial y no directamente relacionada con el servicio militar, sino con respecto a la profesión. Ante esta ausencia, se espera contribuir con un alcance que ponga en evidencia este espacio muchas veces invisibilizado y complejo, considerando que puede ser prometedor en datos para el análisis de las decisiones políticas que conduzcan a fortalecer el accionar de las instituciones de las Fuerzas Armadas al momento de convocar al personal militar voluntario y futuras políticas públicas para la juventud.
Regarding the Peruvian voluntary military service: A review of the latest debates that address the constitutional exercise in contemporary Peru
Keywords: Military Service; Voluntary Military Service; Youth; Servicio militar; Servicio militar voluntario; Juventud; COVID-19 (Enfermedad); https://purl.org/pe-repo/ocde/ford#5.04.03